Prothrombotic changes due to an increase in thyroid hormone levels - Horacek, Jiri; Maly, Jaroslav; Svilias, Ioannis; Smolej, Lukas; Cepkova, Jitka; Vizda, Jaroslav; Sadilek, Petr; Fatorova, Ilona; Zak, Pavel (European journal of endocrinology, 2015)
OBJECTIVE: With increasing free thyroxine levels, a gradually rising risk of venous thromboembolism has been described in case-control studies. However, reports on the influence of thyroid hormones on haemostasis, while suggesting a hypercoagulable state in thyrotoxicosis, have often been inconclusive. This study evaluates multiple markers of haemostasis and fibrinolysis in a paired design, making it more sensitive to changes in thyroid hormone levels. DESIGN: We analysed multiple variables in patients who shifted from severe hypothyroidism to mild hyperthyroidism during thyroid cancer treatment. Those with possible residual disease were excluded. METHODS: Ninety patients following total thyroidectomy were tested on two occasions: i) before radioiodine remnant ablation and ii) 6 weeks later, on levothyroxine (lT4) suppression treatment, and the results were compared using the Wilcoxon's test for paired data. RESULTS: During lT4 treatment, significant increases (all P<0.001) in fibrinogen (from median 3.4 to 3.8 g/l), von Willebrand factor (from 85 to 127%), factor VIII (from 111 to 148%) and plasminogen activator inhibitor 1 (from 6.5 to 13.9 μg/l) were observed. In addition, the activation times of platelet adhesion and aggregation stimulated with collagen and epinephrine (EPI)/ADP, i.e. closure times in platelet function analyser (PFA-100), were significantly shortened (P<0.001): for EPI from median 148 to 117 s and for ADP from 95 to 80 s. Changes in other tests were less prominent or insignificant. CONCLUSIONS: An increase in thyroid hormone levels shifts the haemostatic balance towards a hypercoagulable, hypofibrinolytic state. This may contribute to the increased cardiovascular morbidity and mortality observed even in mild thyrotoxicosis.
Keywords: thyroxin; Fibrinolysis; hypertyreóza; Hormone Replacement Therapy; Platelet Function Tests; hormonální substituční terapie; koagulační faktory; trombóza; hormony štítné žlázy; mužské pohlaví; Thyroidectomy; Adult; nádory štítné žlázy; Thyroid Hormones; fibrinolýza; radioizotopy jodu; Postoperative Complications; Thrombosis; vyšetření funkce trombocytů; ženské pohlaví; Blood Coagulation Factors; Thyroid Neoplasms; Humans; tyreoidektomie; Hyperthyroidism; Thyroxine; dospělí; Female; pooperační komplikace; Iodine Radioisotopes; lidé; Male